Applicability of the mixed-mode controlled double cantilever beam test and related evaluation methods. (August 2020) - Bödeker, Felix; Marzi, Stephan
Highlights: Numerical study on recently presented MC-DCB test in mixed-mode I + III. Identification and quantification of sensitivities of MC-DCB test based on FE simulations. Limitations and capabilities of identification methods for traction at crack tip. Proposal of control strategies for MC-DCB test series. Abstract: Recently, a novel methodology has been proposed to study non-linear fracture in mixed mode I + III, aimed at directly identifying constitutive laws regarding cohesive zone modeling from experimental data. In the case of adhesive joints, cohesive laws in the mixed mode have been derived by applying this methodology. This study discusses theoretical aspects of the novel methodology and investigates the proposed test setup by numerical simulations. This provides information on the sensitivity and limitations of the methodology, which is based on the J -integral approach.